Protective role of Garlic Oil Pre-and Post-Infection of Mycoplasma agalactia in Albino mice - Zainab Hashim.Rida,; Zainab Ismail Ibrahim, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The present study aimed to evaluate the effect of garlic oilextraction (GOE) on interleukin18 (IL18) in albino mice before and after infection with mycoplasma agalactia. Thirty Balb/c mice were allocated into three groups:1) G: mice treated with 100 mg \kg of garlic oil orally for30 before and after infection with mycoplasma agalactia: 2) P: mice infected with mycoplasma agalactia for 30 days without any treatment; 3) N: control group.The isolation was obtained by culturing milk samples from goats and sheep.the mice infected with mycoplasma agalactiaintraperitoneally.The clinical signs are reported from infected mice daily and after a month of infection the mice are euthanized and IL18 was measured using, indirect enzyme-linked immunosorbent assay (ELISA), in addition to the male reproductive system histopathological examination. The results showed the effectiveness of garlic oil in reducing infection, as there was a significant increase in the level of IL18 in mice treated with garlic oil compared to the control group. The IL18 was 273.45 in the treated group with garlic oil, compared to 40.86 in the appositive control group and 7.49 in the negative control group.Histopathological examination of the testis showed subcapsular infiltration of inflammatory cells and degeneration.